Pendekatan Proses Pengidentifikasian Pengetahuan Perusahaan untuk Memaksimalkan Akselerasi Sebagai Landasan Knowledge Management System - Ce, Win (ComTech: Computer, Mathematics and Engineering Applications, 2011)
The high increment of competition currently requires companies to have more values to offer to customers. Company must also truly understand what the core of the companies is as the reason of customers continuing the cooperation with the company. In its growth of knowledge management it clearly provide direction and a real acceleration to the company. The biggest problem is the lack of the ability of companies to see and identify the main knowledge and the main core in the company. This study discusses the best approach to identify the existing knowledge in the company as the basis for the development of the companies and for the construction of knowledge management system.